(3HdZI GdXQaGA aj PcQi JhGQjN GdNdaGAs - (3CHh GdMSf Ydj Hf CHh YHO Gddg eMeO Hf CHj GdSQhQ Hf YHO GdQMef GdQhMjs
(3ChdgG (B:s
(3CeG HYO aEfi PGcQ ai cJGHj gPG fSH QShd Gddg Udi Gddg Ydjg hSde hfPcQ CjVkG fSH ef Qhi HYOg GdNdaGA GdQGTOjf hZjQge ef GdNdaGA GdeTghQjf s
(3BNQgG (B:s
(3hcSQJ GdaQfL ai CjGeg ai ZRhI SfI KeGf hCQHYjf hSJeGFI s
(3GfXQ HQbe (B934 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B585 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B67 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs